Academic Resilience and Academic Performance Among Postgraduate Students at Dharanidhar University, Keonjhar, India - Priyabrata Sahoo; Parshuram Sahoo (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2026)
The present study investigates the relationship between academic resilience and academic performance among postgraduate students of Dharanidhar University, Keonjhar. Academic resilience defined as a student’s ability to effectively cope with academic challenges and plays a crucial role in determining educational success. Existing studies often overlook contextual factors such as institutional environment and gender. Additionally, there is a lack of empirical data analyzing the relationship between these variables from regional universities like Dharanidhar University, Keonjhar. The study aimed to assess academic resilience, academic performance and determine the correlation among postgraduate students. This quantitative survey research design was adopted with a sample of 100 postgraduate students selected through simple random sampling from Dharanidhar University. Data was gathered through the researcher developed Standardized questionnaire to measure academic resilience. Academic performance was measured using the students Semester Grade Point Average (SGPA) of the last semester. The data were analyzed using appropriate statistical techniques, including percentage analysis and Pearson correlation. The findings revealed that the positive relationship between academic resilience and academic performance confirms that strengthening resilience can directly contribute to better educational outcomes. This study also emphasizes the importance of educational institutions adopting holistic approaches to student development by addressing not only academic growth but also emotional and psychological well-being. Moreover, parents and educational stakeholders should work collaboratively to provide guidance, encouragement, and emotional support to students.